Role of Actin Filament Network in Burkholderia multivorans Invasion in Well-Differentiated Human Airway Epithelia - Schwab, Ute E. (American Society for Microbiology, 2003)
The role of the actin-based cytoskeleton in the internalization process of Burkholderia multivorans by well-differentiated human airway epithelia was investigated by immunohistology and confocal microscopy. Our data suggest that an intact actin cytoskeleton is required for biofilm formation but not single cell entry or paracytosis.